Alimas Plastic Industries Sdn. Bhd. / Nur Almas Ahmad - Ahmad, Nur Almas (2020)
The company of Alimas Plastic Industries Sdn. Bhd is a form of business based on partnership which is four members that involved which have the important position in my company such as administration manager, marketing manager, operational manager and financial manager. This company prepared several of plastic products using the raw material that specific for process the products only. It is located at Dungun, Terengganu. Alimas Plastic Industries Sdn. Bhd more focuses on production of plastic which is it wanted from customers nowadays because it is always used and at the same time not have expired date. So, customers can store the product first and use when necessary. Among the differences of our products with other company are we use a high quality products and take raw material from suppliers that offer the affordable price for company so that company of Alimas Plastic Industries Sdn. Bhd not need to take out a lot of money for produce the products. To attract the customers, we offer the special gift for our special customers who was come buy wholesale products, will get the free container plastic that given. There are some research I did which is majority of other company in produce the same type of products not give the free gift like my company of Alimas Plastic Industries Sdn. Bhd. In addition, other getting a profit from the company's products, I also practice my workers with selling while by giving the gift.